Dihydrotestosterone synthesis in the sheep corpus luteum and its potential mechanism in luteal regression. Issue 9 (22nd January 2019) - Xiao, Longfei; Song, Liangli; Hu, Junjie; Zhang, Quanwei; Jiang, Yuting; Duan, Hongwei; Zhang, Yong; Zhao, Xingxu; Hua, Yongli
Abstract: Corpus luteum (CL) regression is a complex physiological process. Previous studies have shown that dihydrotestosterone (DHT) may be involved in regulating CL regression, but the mechanism is still unclear. In this study, we evaluated the localization of the two isoforms of DHT synthetase 5α‐reductase (5α‐red1 and 5α‐red2) and androgen receptor (AR) in sheep CL, and investigated 5α‐red1, 5α‐red2, AR, and DHT levels at different luteal stages of CL (early, middle, and late phase) by immunohistochemistry, quantitative real‐time polymerase chain reaction, and western blot analysis. Moreover, we cultured luteal cells from middle phase CL and treated them with different concentrations of DHT (10 −10 –10 −6  M) and the AR antagonist flutamide (10 −5  M), to evaluate whether DHT is involved in the regulation of progesterone (P4) secretion and progesterone nuclear receptor (PGR) expression and whether these effects are regulated by the AR pathway. We also investigated the effects of DHT and flutamide on prostaglandin F2α (PGF2α) secretion and apoptotic gene and protein expression. Our results showed that 5α‐red1, 5α‐red2, and AR were expressed in the CL, and their expression and DHT levels were changed during the luteal phase. DHT was involved in mediating P4 and PGF2α secretion and PGR and apoptotic gene and protein expression. The effects of DHT on CL were at least partially regulated by the AR pathway. This study reveals the mechanism of action of DHT on sheep CL regression and lays the foundation for further exploration of androgen regulation of CL function.